2019
DOI: 10.3390/antiox8100491
|View full text |Cite
|
Sign up to set email alerts
|

Effect οf Genotype and Growing Year on the Nutritional, Phytochemical, and Antioxidant Properties of Industrial Hemp (Cannabis sativa L.) Seeds

Abstract: Cannabis sativa L. seeds have been an important source of protein, oil, and dietary fiber for human and animals. Currently, there is a growing interest in the commercial products of these seeds, which are recognized as a legitimate source of medicaments, cosmeceuticals, and nutraceuticals. The objective of this study was to investigate the nutritional, phytochemical composition, and antioxidant properties of seeds from seven hemp cultivars grown in Greece for three consecutive years. All the measured parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 43 publications
(70 reference statements)
14
117
1
9
Order By: Relevance
“…68 Hempseeds provide *500-600 Kcal/100 g of product and are composed of approximately one-fourth of proteins, one-fourth of carbohydrates, and one-third of fat, 69 with some significant variations among different genotypes. 70 Hempseeds are rich in polyunsaturated fatty acids, which also vary among different genotypes. One study of seven different hempseed cultivars (''Bialobrzeskie,'' ''Felina 32,'' ''Tygra 75,'' ''Futura 27,'' ''Santhica,'' ''Fedora 17,'' and ''Finola'') showed that ''Finola'' had the highest content of c linolenic and a-linolenic acids and the lowest content in oleic acid and saturated fatty acids, such as palmitic and stearic acids.…”
Section: Hemp Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Hempseeds provide *500-600 Kcal/100 g of product and are composed of approximately one-fourth of proteins, one-fourth of carbohydrates, and one-third of fat, 69 with some significant variations among different genotypes. 70 Hempseeds are rich in polyunsaturated fatty acids, which also vary among different genotypes. One study of seven different hempseed cultivars (''Bialobrzeskie,'' ''Felina 32,'' ''Tygra 75,'' ''Futura 27,'' ''Santhica,'' ''Fedora 17,'' and ''Finola'') showed that ''Finola'' had the highest content of c linolenic and a-linolenic acids and the lowest content in oleic acid and saturated fatty acids, such as palmitic and stearic acids.…”
Section: Hemp Foodmentioning
confidence: 99%
“…One study of seven different hempseed cultivars (''Bialobrzeskie,'' ''Felina 32,'' ''Tygra 75,'' ''Futura 27,'' ''Santhica,'' ''Fedora 17,'' and ''Finola'') showed that ''Finola'' had the highest content of c linolenic and a-linolenic acids and the lowest content in oleic acid and saturated fatty acids, such as palmitic and stearic acids. 70 Hempseed proteins represent a valuable source of sulfur-containing amino acid methionine and cystine and provide high quantities of arginine, an essential amino acid with beneficial cardiovascular properties. Accumulating evidence supporting the antihypertensive effect of hydrolyzed hempseed proteins, possibly mediated by inhibition of angiotensin-converting enzyme and renin, 71 provided the rationale for an ongoing human trial testing hemp protein powder as an antihypertensive nutritional intervention.…”
Section: Hemp Foodmentioning
confidence: 99%
“…Hemp by-product oxygen radical absorbance capacity (ORAC) values are, however, lower than αtocopherol (1,293 µm TE/g) (69), and ORAC values are thought to be more reflective of antioxidant capacity in biological systems (70). Phenol amides (i.e., N-trans-caffeoyl-tyramine), lignanamides (i.e., cannabisin A, B, and C) (46,71), tocopherols (42,61) and CBD (11) are the major elements contributing to the antioxidant capacity of hempseed by-products. Chen et al (71) and Irakli et al (46) narrowed this list to N-trans-caffeoyltyramine, cannabisin A, B, and C as the major antioxidant phenolic compounds of hemp.…”
Section: In Vitro Bioactivity Of Phytochemicals In Hemp By-products Amentioning
confidence: 99%
“…In addition, hemp seeds have a lot of natural antioxidants such as phenolic compounds, phytosterols, and tocopherols, which may play a role in reducing the risk of chronic diseases, including cancer, lipid metabolism, dermatological diseases, and cardiovascular health, and prevent the oxidation of unsaturated fatty acids (Irakli et al., 2019).…”
Section: Introductionmentioning
confidence: 99%